Blood-stage antiplasmodial activity and oocyst formation-blockage of metallo copper-cinchonine complex - Morais, Camila Martins Gomes; Brito, Ramayana Morais de Medeiros; Weselucha-Birczyńska, Aleksandra; Pereira, Valeska Santana de Sena; Pereira-Silva, Jordam William; Menezes, Alexandre; Pessoa, Felipe Arley Costa; Kucharska, Martyna; Birczyńska-Zych, Malwina; Ríos-Velásquez, Claudia María; Andrade-Neto, Valter Ferreira de (Frontiers in Cellular and Infection Microbiology, 2022)
In the fight against malaria, the key is early treatment with antimalarial chemotherapy, such as artemisinin-based combination treatments (ACTs). However, Plasmodium has acquired multidrug resistance, including the emergence of P. falciparum strains with resistance to ACT. The development of novel antimalarial molecules, that are capable to interfere in the asexual and sexual blood stages, is important to slow down the transmission in endemic areas. In this study, we demonstrate the ability of the mettalo copper-cinchonine complex to interfere in the sexual and asexual stages of Plasmodium. The tested compounds in the in vitro assay were cinchonine derivative, named as CinCu (Bis[Cinchoninium Tetrachlorocuprate(II)]trihydrate). Its biological functions were assessed by antiplasmodial activity in vitro against chloroquine-resistant P. falciparum W2 strain. The mice model of P. berghei ANKA infection was used to analyze the antimalarial activity of CinCu and Chloroquine and their acute toxicity. The oocyst formation-blocking assay in Anopheles aquasalis was performed using P. vivax infected blood, which was treated with different concentrations of CinCu, Cinchonine, and Primaquine. We found that CinCu was able to suppress as high as 81.58% of parasitemia in vitro, being considered a molecule with high antiplasmodial activity and low toxicity. The in vivo analysis showed that CinCu is a partially active molecule against the blood-stage forms of P. berghei ANKA, without inducing severe clinical signs in the treated groups. The transmission-blocking assay revealed that both Cinchonine and Primaquine were able to reduce the infection intensity of P. vivax in A. aquasalis, leading to a decrease in the number of oocysts recovered from the mosquitoes’ midgut. Regarding the effect of CinCu, the copper-complex was not able to induce inhibition of P. vivax infection; however, it was able to induce an important reduction in the oocyst intensity. The use of higher concentrations of CinCu used as transmission blockers still need further investigation. Furthermore, our study can draw a new pathway for the repositioning of already known antimalarial drugs, by editing their chemical structure and how the cooper-coordination complexes can improve the antimalarial activity against both asexual and sexual stages of the parasite.